2023
DOI: 10.1038/s41598-023-35968-x
|View full text |Cite
|
Sign up to set email alerts
|

Local and wide-scale livestock movement networks inform disease control strategies in East Africa

Abstract: Livestock mobility exacerbates infectious disease risks across sub-Saharan Africa, but enables critical access to grazing and water resources, and trade. Identifying locations of high livestock traffic offers opportunities for targeted control. We focus on Tanzanian agropastoral and pastoral communities that account respectively for over 75% and 15% of livestock husbandry in eastern Africa. We construct networks of livestock connectivity based on participatory mapping data on herd movements reported by village… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…While two distinct seasons, wet and dry, are generally recognised, rainfall patterns are becoming increasingly inconsistent and unpredictable, resulting in long periods without rain even in the wet seasons and extended dry seasons and droughts [9,25]. Ekwem et al [15] showed that the change in rainfall patterns drove unplanned livestock movements, especially during drought. As temperature and precipitation are predicted to increase in the future, and East Africa is more influenced than most other parts of the world [7][8][9]25], we hypothesise that the stresses on resources induced by climate change are likely to result in an overall more connected livestock population, with implications for infectious disease risks and therefore human and animal health.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While two distinct seasons, wet and dry, are generally recognised, rainfall patterns are becoming increasingly inconsistent and unpredictable, resulting in long periods without rain even in the wet seasons and extended dry seasons and droughts [9,25]. Ekwem et al [15] showed that the change in rainfall patterns drove unplanned livestock movements, especially during drought. As temperature and precipitation are predicted to increase in the future, and East Africa is more influenced than most other parts of the world [7][8][9]25], we hypothesise that the stresses on resources induced by climate change are likely to result in an overall more connected livestock population, with implications for infectious disease risks and therefore human and animal health.…”
Section: Discussionmentioning
confidence: 99%
“…To project future patterns we considered the impact of changes in the seasonal pattern of movements caused by changes in precipitation, due to its influence on the availability of pasturelands and water. Previous studies have shown that the frequency of use of resource areas is related to resource availability, which in turn is influenced by season [5, 15]. While two distinct seasons, wet and dry, are generally recognised, rainfall patterns are becoming increasingly inconsistent and unpredictable, resulting in long periods without rain even in the wet seasons and extended dry seasons and droughts [9, 25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations